The Role of Islamic Education Teachers in Cultivating Religious Character: A Case Study of Boarding School-Connected Vocational Education - Reyna Herlina Sindi; Imam Wahyono; Nurul Fatimah; Kholilur Rahman (Al-Qalam Institue, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in shaping students’ religious character by examining their roles as educators, role models, mentors, and supervisors-partners. The research addresses the need to strengthen students’ religious character amid challenges related to worship discipline, moral consistency, and social influences in vocational education. This study employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, observation, and documentation involving seven purposively selected informants consisting of PAI teachers and students. Data validity was ensured through source and technique triangulation, member checking, and audit trails, while data analysis followed the interactive model of Miles and Huberman, including data condensation, data display, and conclusion verification. The findings reveal that PAI teachers play interconnected roles in developing students’ religious character through the integration of Islamic values in learning, exemplary behavior, religious habituation, continuous guidance, and behavioral supervision. The study implies that effective religious character education requires collaboration among teachers, schools, families, and educational environments to ensure the consistent internalization of religious values in students’ daily lives.